On the strong P-regular splitting iterative methods for non-Hermitian linear systems - Lu, Junxiang; Zhang, Chengyi (AIMS mathematics, 2021)
The strong P -regular splitting is put forward and defined for iterative methods of non-Hermitian linear systems in the paper. The strong P -regular splitting combining SOR iterative methods and relaxed SOR iterative methods are established, and conditions guaranteeing the convergence are presented. Furthermore, two numerical experiments are done to illustrate the convergence and effectiveness of our iterative methods.